Pendidikan Karakter Menurut Perspektif Muhammad Athiyah Al-Abrasyi: Suatu Analisis Historis-Filosofis - Sulhan Yus; Warul Walidin (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Character education is very important in educating each individual to become a human being with good character and noble character. Today we see many people who have taken a very high education but do not have noble morals, so they often do things that have been prohibited by religion. The focus of this research is to explore the thoughts and opinions of Muhammad Athiyyah Al-Abrasyi regarding character education in the realm of Islamic teaching. This research applies the library research method, by collecting data through books, journals, articles, and various literatures relevant to the object of research, especially the writings of Muhammad Athiyyah Al-Abrasyi. The results showed that character education according to Muhammad Athiyah Al-Abrasyi is started by instilling character education since humans are at an early age or when they are in childhood, also emphasizing on harmonizing traditional Islamic education with the times or modernizing the Islamic teaching system. Muhammad Athiyah Al-Abrasyi also requires the importance of balance between ukhrawi and worldly actions, so as to create Islamic humans who are civilized, ethical, moral, and have qualified abilities in carrying out their daily lives.